iPad secrets : do what you never thought possible with your iPad - Murph, Darren (Indianapolis, IN : John Wiley & Sons, 2012)
Explores the little-known features of the iPad, offering advice, tips, and tricks on iCloud integration, FaceTime, and iMessage.
'Covers iPad, iPad 2, and 3rd Generation iPad!'--Cover.
Includes index.
Keywords: iPad (Computer); Tablet computers; iPad (Computer); Portable computers